Ho Chi Minh's Educational Philosophy: A Framework for Fostering National Identity and Global Citizenship - Phan Thi Kim Lien (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This study explores Ho Chi Minh’s educational philosophy as a strategic framework for cultivating national identity and global citizenship within the context of Vietnam’s educational reform toward 2030. Employing a qualitative method with a descriptive-analytical approach through documentary research, this study analyzes the principle of "planting people" (trồng người) and the dialectic between Hồng (revolutionary morality) and Chuyên (professional competence). The results indicate that Ho Chi Minh’s philosophy provides a robust ontological foundation for holistic human development, capable of balancing the preservation of traditional values with the demands of international integration. The study also finds that the concept of global citizenship in Vietnamese education is a modern manifestation of Ho Chi Minh’s pure internationalist spirit. The conclusion asserts that this philosophy remains a relevant compass for building students' moral resilience and technical proficiency in the era of the Fourth Industrial Revolution. Policy recommendations include the integration of digital ethics and the strengthening of local cultural identity within the curriculum to address the challenges of global homogenization.